MALL SUKARAMI PALEMBANG - Alvin Gozali; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2021)
Humans are social creatures, therefore humans really need public space to interact with one another. Apart from being useful for interaction, public spaces can also be used to meet the needs of habitation and become the background for the development of human life, both in social, economic, cultural and entertainment activities. However, the lack of adequate public space in an area will make the area underdeveloped and make it difficult for the people of the area to meet the needs of the community. The design of the Sukarami Mall program is a public space divided into 2 main programs which are shopping to meet needs and supporting programs that are recreational in nature, where the main program is a shopping program that accommodates people's needs in the form of clothing, food, shelter, while recreational support is used for meet the needs of society. Where this program is the background of regional development in terms of regional, socio-economic and entertainment. in the shopping space program, it focuses more on daily shopping needs, while the recreational support program is oriented towards culinary and hangout recreation. Keywords: mall; sukarami palembang; shopping center AbstrakManusia merupakan makhluk sosial maka dari itu manusia sangat membutuhkan ruang publik untuk berinteraksi satu dengan yang lainnya. Selain berguna untuk berinteraksi, ruang publik juga bisa untuk memenuhi kebutuhan berhuni dan menjadi latar belakang perkembangan kehidupan manusia, baik dalam kegiatan sosial ,ekonomi , budaya maupun hiburan. Namun kurangnya ruang publik yang memadahi disebuah kawasan akan membuat kawasan tersebut menjadi keterbelakangan dan membuat masyarakat kawasan tersebut menjadi sulit untuk memenuhi kebutuhan berhuni masyarakat. Rancangan program Sukarami Mall ini merupakan ruang publik yang dibagi menjadi 2 program utama yang bersifat perbelanjaan untuk memenuhi kebutuhan dan program penunjang yang bersifat rekreasi, dimana program utama merupakan program perbelanjaan yang mengakomodir kebutuhan masyarakat berupa kebutuhan sandang ,pangan, papan, sedangkan penunjang rekreasi guna untuk memehuni kebutuhan bersosisali masyarakat. Dimana program ini kan menjadi latar belakang perkembangan kawasan dari segi, sosial ekonomi dan hiburan kawasan. pada program ruang perbelanjaan lebih memfokuskan kepada kebutuhan berbelanja harian, sedangkan program penunjang rekreasi berorientasi ke rekreasi bidang kuliner dan tongkrongan.